Motoric Cognitive Risk Syndrome: Symptoms, Pathology, Diagnosis, and Recovery - Xiang, Ke; Liu, Yin; Sun, Li (Frontiers in Aging Neuroscience, 2022)
Motoric cognitive risk (MCR) syndrome is a pre-dementia condition, marked by enhanced risk for Alzheimer’s disease and vascular dementia, together with falls, disability and abnormal movements. Research studies revealed distinct neurological and non-neurological clinical gait irregularities during dementia and accelerated functional decline, corresponding to the different MCR subtypes. The disabling characteristics of MCR include balance impairment, postural instability and altered afferent sensory and efferent motor responses. Vertigo and dizziness are common complaints along with aberrant signals from vestibular systems and memory processing, particularly in the elderly. The pathological basis of MCR relates with frontal lacunar infarcts, white matter hyperintensity and grey matter atrophy in premotor and prefrontal cortex that predominantly govern motor planning, coordination, sustained attention and memory. Further, cerebrovascular lesions and cardiovascular disorders exacerbate the disease pathology. Diagnosis of MCR is quite analogous to Mild Cognitive Impairment, through neuropsychological tests, biomarker assays, pathological validation, imaging studies, standardized questionnaire-based evaluation, added to motor function tests, depending on walking speed, dual-task gait tests and ambulation ability. An early diagnosis is important for appropriate treatment and care in MCR. Recovery from MCR may include administration of symptomatic drugs, cognitive, physical and social activities, exercise, diet, nutritional supplements and lifestyle habits that restrict the disease progression. Psychotherapeutic counseling, anti-depressants and vitamins may support motor and cognitive improvement, primarily through restorative pathways. Overall, the current review informs the vital connection between gait performance and cognition in MCR, and highlights the usefulness of future research in the understanding and treatment of dementiating illness.